Defeating phonological-core deficit among dyslexic children by activating arousal dimension of affective impressions - Aziz, Fakhrul Anuar; Husni, Husniza; Jamaludin, Zulikha (International Association of Technology, Education and Development (IATED), 2008)
Dyslexic children, due to their phonological-core deficits, face serious impairment in reading skills and found reading a hassle. One way to assist them in reading is using computer-based application so that the vital skills can be developed and matured. However, such applications for dyslexic children must be special in the sense that it has to have some affective quality attributes to constantly encourage and motivate them towards reading. This paper illustrates and compares factors that serve as affective quality in reading applications meant for those children. These qualities are recognised through persons we created as a result of profiling the dyslexic children under study. The profiles selected as primary persons produce requirements which are of encouragement and motivational attributes. These are attributes of affective quality which act as stimuli towards using any application for maximum benefit. It is hoped that the affective quality generated can be of great significance towards the installment of positive feelings and perception in reading for dyslexic children.